Linker Histone H1.4 Inhibits the Growth, Migration and EMT Process of Non-Small Cell Lung Cancer by Regulating ERK1/2 Expression - Qian Chen; Mengqi Yang; Xinyue Duan; Jie Zhang; Fan Shi; Rong Chen; Yong Li (Biochemical Genetics, 2025)

Functional Analysis of Sheep POU2F3 Isoforms - Guang-Wei Ma; Yan-Kai Chu; Hua Yang; Xiao-Hong Yan; En-Guang Rong; Hui Li; Ning Wang (Biochemical Genetics, 2020)
POU domain class 2 transcription factor 3 (POU2F3) plays an important role in keratinocyte proliferation and differentiation. Our previous study identified four sheep POU2F3 transcript variants ( POU2F3-1 , POU2F3-2 , POU2F3-3 , and POU2F3-4 ), encoding three POU2F3 protein isoforms (POU2F3-1, POU2F3-2, and POU2F3-3). However, the functional differences among the three POU2F3 isoforms remain unknown. The objective of this study was to determine the tissue expression pattern of the four POU2F3 transcript variants in sheep and to investigate the functional differences in cell proliferation among the three POU2F3 isoforms. Quantitative RT-PCR analysis showed that the four POU2F3 transcripts were ubiquitously expressed in all tested adult sheep tissues, and POU2F3-1 exhibited higher expression level than the other three POU2F3 transcript variants in skin ( P P P P > 0.05). Dual luciferase reporter assays demonstrated that overexpression of any one of the three POU2F3 isoforms significantly inhibited the promoter activities of keratin 14 ( KRT14 ) and matrix metalloproteinase 19 ( MMP19 ) genes ( P KRT14 and MMP19 genes than POU2F3-1 and POU2F3-2 ( P P > 0.05). These results suggest three sheep POU2F3 isoforms have similar functional effects, but to a different extent.

Genotypic Analysis of Multidrug-Resistant Mycobacterium tuberculosis Isolates Recovered From Central China - Shu-Lin Zhang; Hua Qi; Dun-Lian Qiu; Da-Xu Li; Jie Zhang; Chang-Mei Du; Guo-Bin Wang; Zhi-Rong Yang; Qun Sun (Biochemical Genetics, 2007)